Anal Cancer: Emerging Standards in a Rare Disease. Issue 24 (20th August 2022) - Eng, Cathy; Ciombor, Kristen K.; Cho, May; Dorth, Jennifer A.; Rajdev, Lakshmi N.; Horowitz, David P.; Gollub, Marc J.; Jácome, Alexandre A.; Lockney, Natalie A.; Muldoon, Roberta L.; Washington, Mary Kay; O'Brian, Brittany A.; et al.
Abstract : The social stigma surrounding an anal cancer diagnosis has traditionally prevented open discussions about this disease. However, as recent treatment options and an increasing rate of diagnoses are made worldwide, awareness is growing. In the United States alone, 9, 090 individuals were expected to be diagnosed with anal cancer in 2021. The US annual incidence of squamous cell carcinoma of the anus continues to increase by 2.7% yearly, whereas the mortality rate increases by 3.1%. The main risk factor for anal cancer is a human papillomavirus infection; those with chronic immunosuppression are also at risk. Patients with HIV are 19 times more likely to develop anal cancer compared with the general population. In this review, we have provided an overview of the carcinoma of the anal canal, the role of screening, advancements in radiation therapy, and current trials investigating acute and chronic treatment–related toxicities. This article is a comprehensive approach to presenting the existing data in an effort to encourage continuous international interest in anal cancer.